(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Plant requires suitable soil for higher yield, quality growth and desired crop productivity that differ with soil characteristics, availability of the nutrient elements and overall soil fertility. Aloe vera, a documented medicative plant, is used for numerous medical and cosmetic applications since very beginning of the civilization. An experiment was conducted in Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh to find out the most appropriate soil for A. vera cultivation. Seven types of soils viz., acid, calcareous, non-calcareous, charland, saline, peat and acid sulphate were collected from different locations of Bangladesh. Eighteenth month old Aloe vera seedlings were collected from Shomvogonj, Mymensingh and planted during last week of May, 2017 following completely randomized design (CRD) with three replications. Most of the soils were light grey in colour, acidic to neutral in nature and clay to clay loam in texture except non-calcareous and charland soils. Bulk density, particle density and field capacity ranged from 1.23−1.45 g cm−3, 2.20−2.58 g cm−3 and 27.07−30.20%, respectively. The ranges of pH, EC and organic matter contents were 3.8 to 7.8, 0.25 to 14.04 dS m−1 and 0.88 to 16.40%, respectively. The organic matter content was found as low to moderate except peat soil. Total N, exchangeable K, available P and S contents ranged from 0.05−0.95%, 0.17−0.73 cmol kg−1, 3.09−12.10 and 11.06−735.12 µg g−1 soil, respectively. Growth and leaf biomass yield of A. vera was significantly influenced by different soil types. The highest plant height, leaf number, leaf area and leaf fresh weight were recorded from the plant grown in non-calcareous soil whereas maximum fresh gel weight, dry leaf weight and yield increase over acid sulphate soil were found from the plant grown in calcareous soil. The highest fresh leaf gel weight (907 g plant−1) was obtained from the plant grown in calcareous soil which was identical with the gel weight (880 g plant−1) of the plant grown in acid soil. The yield increase of acid, non-calcareous, charland, saline1 (6.32 dS m−1) and saline2 (8.14 dS m−1) soils over acid sulphate soil were 718, 712, 394, 144 and 86%, respectively. The overall performance of the soils in relation to leaf biomass yield was of the following order: calcareous ≥ acid ≥ non-calcareous > charland > saline1 (6.32 dS m−1) > saline2 (8.14 dS m−1) > peat > acid sulphate soil. The results suggest that farmers could be advised to grow A. vera either in calcareous or acid soils of Bangladesh. Since calcareous and non-calcareous soils are mostly used for growing cereals, pulses, cash crop like sugarcane, fruits etc., acid soil could be used for cultivating this important medicinal crop considering the socio-economic conditions of the country. J. Bangladesh Agril. Univ. 16(3): 448–456, December 2018